Estudo da microestrutura do aço inoxidável duplex uns s31803 (saf 2205) quando submetido a tratamentos térmicos de envelhecdimento nas temperaturas de 500 A 700° C - Pinheiro, Antonio Matheus Barbosa (Universidade Federal Rural do Semi-Árido, 2018)
Duplex stainless steels are high mechanic resistance materials with good corrosion resistance, which explain the large application of this class of materials on petrochemical and chemical sector. The excellent properties of these materials are attributed to the biphasic microstructure with equal parts of ferrite and austenite, and also to the Cr, Ni, Mo and N additions. This work investigates microstructural changes between 500 ° C and 700 ° C for UNS S31803 steel (SAF 2205). The material under study was submitted to the thermal treatment of aging in the temperatures of 500 ° C, 600 ° C and 700 ° C in the times of 6h, 12h and 27h. Next, the microstructural characterization was carried out by optical microscopy using two different types of solutions in the attack of the samples, in addition, the percentage of the phases present in the samples was quantified using a computational program. The Vinckers microhardness test (0.025 HV) was used in the aging time of 27 h, where the sigma phase precipitation (σ) occurs at temperatures of 600 ° C and 700 ° C due to the reduction of ferrite. an increase in the microhardness of the ferrite after increasing the heat treatment time. It was inferred that in the aging conditions imposed by the increase in time and temperature in the heat treatment there will be a reduction in the mechanical strength of the SAF 2025 duplex steel.
Monografia
Keywords: Aço inoxidável dúplex; Tratamento térmico; Microdureza; SAF 2205; Stainless steel duplex; Heat treatment; Microhardnes; ENGENHARIAS::ENGENHARIA MECANICA